Fluorinated Graphene Contacts and Passivation Layer for MoS2 Field Effect Transistors. (9th March 2022) - Ryu, Huije; Kim, Dong‐Hyun; Kwon, Junyoung; Park, Sang Kyu; Lee, Wanggon; Seo, Hyungtak; Watanabe, Kenji; Taniguchi, Takashi; Kim, SunPhil; van der Zande, Arend M.; Son, Jangyup; Lee, Gwan‐Hyoung
Abstract: Realizing a future of 2D semiconductor‐based devices requires new approaches to channel passivation and nondestructive contact engineering. Here, a facile one‐step technique is shown that simultaneously utilizes monolayer fluorinated graphene (FG) as the passivation layer and contact buffer layer to 2D semiconductor transistors. Monolayer graphene is transferred onto the MoS2, followed by fluorination by XeF2 gas exposure. Metal electrodes for source and drain are fabricated on top of FG‐covered MoS2 regions. The MoS2 transistor is perfectly passivated by insulating FG layer and, in the contacts, FG layer also acts as an efficient charge injection layer, leading to the formation of Ohmic contacts and high carrier mobility of up to 64 cm 2 V −1 s −1 at room temperature. This work shows a novel strategy for simultaneous fabrication of passivation layer and low‐resistance contacts by using ultrathin functionalized graphene, which has applications for high performance 2D semiconductor integrated electronics. Abstract : This paper reports a facile technique that simultaneously utilizes monolayer fluorinated graphene (FG) as the passivation layer and contact buffer layer to 2D semiconductor transistors. The MoS2 transistor is perfectly passivated by insulating FG, and the device shows excellent performance with Ohmic contacts, high on/off ration of 10 5, and high carrier mobility of up to 64 cm 2 V −1 s −1 at room temperature.